Myopathy due to concominant use of statin and gemfibrosil in a patient with chronic renal failure: Case report - (:unkn) unknown (My University, 2004)
Lipid lowering agents including fibric acid derivatives (fibrates) and HMG-CoA reductase inhibitors (statins) can result in the development of a primarily proximal lower extremity myopathy, occasionally associated with myoglobinuria. These adverse effects increase when the patients are treated concomitantly with statins and fenofibrates or statins and gemfibrozils. We present a case of chronic renal failure accompanied by acute muscle pain and weakness following the daily administration of 600 mg of gemfibrozil for a month in addition to simvastatin treatment. The clinical state of the patient improved dramatically after cessation of both fibrate and statin therapy. In general, patients with a normal renal function seem to tolerate these drugs well, but they must be used with caution in patients with renal or hepatic failure.
Keywords: Chronic renal failure; Creatine kinase; Emfibrozil; Myopathy; Rhabdomyolysis; Statin